Efforts To Prevent Bullying Through "Stop Bullying" Socialization: Perspective Of The Law On Child Protection At Kaliwareng Elementary School - Gilar Rozi Khusaini; Wenny Dwi Kurniati (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The world of education is currently facing a serious problem that occurs to students, namely bullying, which of course has a bad influence on them. This bullying affects the victim to the point of affecting their mental state, causing the perpetrator to act arbitrarily towards the victim. The perpetrator who carries out this action can endanger the physical and emotional health of the victim. The impacts on the victim can be sadness, stress, and mental health disorders, as well as increased anger, and the most deadly of bullying situations is suicide. The purpose of this activity is to educate the school community in general, and students in particular, about various forms of bullying, its dangers, and how to prevent it. Counseling, socialization, and games are used to involve students. Based on initial observations, it was found that 88% of the children, or 44 out of 50 children, had committed verbal bullying. During the activity, the children who were used as objects were fourth grade, fifth grade, and sixth grade, actively participated in activities that ultimately made them aware of the actions they had taken, namely bullying that had bad implications for other students so that they did not repeat it. This project is intended to teach children about different types of bullying behaviors to foster a peaceful and respectful school climate.